Mapping global citizenship: A Bibliometric analysis of the field of education for sustainable development - Pedraja-Rejas, Liliana; Rodríguez-Ponce, Emilio; Laroze, David; Muñoz-Fritis, Camila (Frontiers in Education, 2023)
Since the approval of the Sustainable Development Goals, global citizenship education (GCE) is increasingly capturing the attention of researchers worldwide. In this context, the aim of this manuscript is to review the existing literature on GCE (up to 2021) in journals indexed in the Web of Science. Particularly, it seeks to: 1) document the volume and growth trajectory of knowledge production, 2) identify countries, journals, authors, and key publications (both of the sample analyzed and of the references cited), 3) perform a science mapping of the knowledge base on GCE and 4) discover the thematic foci of empirical works. For this purpose, a bibliometric analysis of the selected articles (n = 350) and a content analysis of the sample’s empirical papers (n = 210) was carried out. The main findings evidence that: the number of articles on the subject has increased notably since 2016; there is a concentration of knowledge production in countries of the Global North, driven mainly by the United States; geographical proximity, and even common language, seem not to be the main factors influencing international scientific collaborations; and, GCE is linked in the empirical articles in the sample mainly to the concept of internationalization of education. The conclusion is that, although the production of knowledge on GCE has recently increased considerably, it continues to lag behind other areas of the educational field.